2017
DOI: 10.3390/met7100393
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution of Intermetallic Compound Formed in Boron Steel Hot-Dipped in Al–7%Ni Alloy

Abstract: Abstract:The microstructural evolution of the intermetallic compound (IMC) layer formed on and in boron steel that was hot dipped in an Al-7Ni (wt %) bath at 690 • C for 30-180 s was investigated, and the growth mechanism of the IMC was identified. Except for the solidification structure of Al, the reaction layer consisted of one layer on the steel surface and two layers in the steel interior. The reaction phase formed on the original surface of the steel was the Al 9 FeNi (T) phase, which has a monoclinic (sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…This is considered beneficial in laser welding. This is the same as the result of the study on the Al-7Ni wt % coating layer that did not contain Si [10]. As shown in Table 3, Nos.…”
Section: Identification Of Phases On Reaction Layers Depending On Varsupporting
confidence: 78%
See 3 more Smart Citations
“…This is considered beneficial in laser welding. This is the same as the result of the study on the Al-7Ni wt % coating layer that did not contain Si [10]. As shown in Table 3, Nos.…”
Section: Identification Of Phases On Reaction Layers Depending On Varsupporting
confidence: 78%
“…In Figure 2a, the Si-free specimen, the R1 layer (No. 4-1) existing between the C layer and the steel structure (S) was formed on the surface of the base material as seen in previous research results [10]. It is suggested that the Al9FeNi (T) phase is formed by the reaction.…”
Section: Classification Of Microstructure Of Coating Layer and Reactisupporting
confidence: 52%
See 2 more Smart Citations
“…Further, it allows the identification of the intermetallic compounds generated at the interface between the SDSS substrate and the aluminum external layer as: Al-Me 3 , Al-Me 2 , Al-Me, Al 7 -Me, Al 3 -Me ( Figure 11 and Table 3). The detected phases also display the same morphology of those identified in the literature [11,55,56].…”
Section: Discussionsupporting
confidence: 70%